Cultural Exchange and the Cold War : Raising the Iron Curtain - Richmond, Yale (Book collections on Project MUSE., 2003)
Some fifty thousand Soviets visited the United States under various exchange programs between 1958 and 1988. They came as scholars and students, scientists and engineers, writers and journalists, government and party officials, musicians, dancers, and athletes-and among them were more than a few KGB officers. They came, they saw, they were conquered, and the Soviet Union would never again be the same. Cultural Exchange and the Cold War describes how these exchange programs (which brought an even larger number of Americans to the Soviet Union) raised the Iron Curtain and fostered changes that prepared the way for Gorbachev's glasnost, perestroika, and the end of the Cold War. This study is based upon interviews with Russian and American participants as well as the personal experiences of the author and others who were involved in or administered such exchanges. Cultural Exchange and the Cold War demonstrates that the best policy to pursue with countries we disagree with is not isolation but engagement.